The present mode of teaching in the ELT classes at the Higher Secondary level in Bangladesh: Is it the practice of CLT or disguised GTM? (Stamford Journal of English, 2013)
This study focuses on the current application of the Communicative Language Teaching (CLT) approach at the higher secondary level in Bangladesh. Several attempts have been taken to prove the justification of the inclusion of the CLT approach in the curriculum in our country. Though the CLT approach was not imposed suddenly on our curriculum, the implementation of CLT in the present context in Bangladesh is still questionable. In this study, concentration has been given to the disguised impact of the Grammar Translation Method (GTM) on the practice of the CLT approach in Bangladesh. It has also been an attempt to find whether we can term the current mode of CLT as modified CLT. This small scale research has been conducted at the Higher Secondary level to locate the presence of GTM in place of the CLT approach. The study has been done through questionnaire survey and interview. The result of the findings has been analyzed and some suggestions have been given on the basis of the result. DOI: http://dx.doi.org/10.3329/sje.v7i0.14459 Stamford Journal of English; Volume 7; Page 1-15